Current Advances in Small Activating RNAs for Gene Therapy: Principles, Applications and Challenges - Zhou, Ling-Yan; He, Zhi-Yao; Xu, Ting; Wei, Yu-Quan (Current Gene Therapy, 2018)
Small activating RNAs (saRNAs) are small double-stranded RNAs that could mediate the target-specific gene expression by targeting selected sequences in gene promoters at both the transcriptional and epigenetic levels. This phenomenon of gene manipulation is known as RNA activation (RNAa), which opens up a new pathway for RNA-based gene therapeutics in contrast to RNA interference. Although the exact molecular mechanism of RNAa mediated by saRNAs still remains foggy, some studies have provided the possible ones to explain it. Furthermore, mounting evidence exhibit that saRNAs not only provide a new approach to study gene function and manipulate transcriptional activity, but also promise a great potential for clinical therapy against various diseases, especially cancer. Cancer-associated genes could be up-regulated by saRNAs to modulate cell cycle and proliferation, induce cell senescence and apoptosis, inhibit cancer cell invasion and migration, and reverse chemotherapy resistance. Herein, we summarize the known mechanisms of saRNAs on up-regulating specific gene expression and focus on the potential applications of saRNAs in gene therapy. In addition, some concerns about mechanisms and challenges for delivery of saRNAs are involved in this review. The precise mechanisms of saRNAs need to be further illustrated and some novel delivery systems for saRNAs are expected to be developed for clinical applications.
Keywords: Small activating RNA